A NEW APPROACH OF MODULAR WATERSHED MODELING WITHIN THE BILATERAL GLOBAL CHANGE PROGRAM WAVES IN NORTHEAST BRAZIL - Heinrichs, Gerold; Voerkelius, Susanne; Voerkelius, Ulrich; Gil, Margarita M. López; Halm, Dietrich; Lang, Ruth; Mörtel, Sebastian; Vieira, Valdira de Caldas Brito (Águas Subterrâneas, 2000)
The city of Picos and the Rio Guaribas Basin in the State of Piauí/Brazil is one of the focus areas within the international WAVES-program. With the investigation in focus areas on meso- and microscale level the statewide, macroscale WAVES-models are evaluated and calibrated. The description and modeling of different water flows in the Rio Guaribas Basin is performed by combining different models or working tools for each water compartment, so-called different modules within the WARIG-concept (WARIG- Modeling of Water Availability and Quality in Rio Guaribas Basin). In addition, the description of the actual water budget and the simulation of future water budgets support the regional development of the investigation area. Further on, results will be up-scaled and transferred to other areas with less data density.